Zapisz w jak najprostszej postaci
-3(1-2y) +½(6-12y)
-(x+2)-2x(x-½)
-(x+7)(x-3)
1-(z+5)(z-1)
uprość wyrażenia
(x+1)²-2x²
-2(3x-1)²+18²
3(2a+1)(2a-1)
(x+8(x-8)-(x²-8)
-(x-4)²+(x+4)²
(3t-1)²-(3t+1(3t-1)

uprość wyrażenia
5*(xy)
-2x*(-3xy)
-4*(-x/2)* (-2x/4)
* razy
1/2 ułamki
prosze tylko dobrze ;]

2

Odpowiedzi

2009-10-06T22:40:39+02:00
Zapisz w jak najprostszej postaci
-3(1-2y) +½(6-12y) = -3 + 6y + 3 -6y = 0
-(x+2)-2x(x-½) = -x - 2 - 2x² + 1 = -2x² - x - 1
-(x+7)(x-3) = -x² + 3x - 7x + 21 = -x² - 4x + 21
1-(z+5)(z-1) = 1 - z² + 1 + 5 + 5 = -z² + 12
uprość wyrażenia
(x+1)²-2x² = x² + 2x + 1 - 2x² = -x² + 2x + 1
-2(3x-1)²+18² = -2(9x² - 6x + 2) + 324 = -18x² + 12x + 320
3(2a+1)(2a-1) = 3 (4a²-1) = 12a² - 3
(x+8)(x-8)-(x²-8) = x² - 64 - x² + 8 = -56
-(x-4)²+(x+4)² = -x² + 8x - 16 + x² + 8x + 16 = 16x
(3t-1)²-(3t+1)(3t-1) = 9t² - 6t + 1 - 9t² + 1 = -6t + 2

2009-10-06T22:45:18+02:00